Pho1a (plastid starch phosphorylase) is duplicated and essential for normal starch granule phenotype in tubers of Solanum tuberosum L - Sharma, Shrikant; Friberg, Martin; Vogel, Paul; Turesson, Helle; Olsson, Niklas; Andersson, Mariette; Hofvander, Per (Frontiers in Plant Science, 2023)
Reserve starch from seeds and tubers is a crucial plant product for human survival. Much research has been devoted to quantitative and qualitative aspects of starch synthesis and its relation to abiotic factors of importance in agriculture. Certain aspects of genetic factors and enzymes influencing carbon assimilation into starch granules remain elusive after many decades of research. Starch phosphorylase (Pho) can operate, depending on metabolic conditions, in a synthetic and degradative pathway. The plastidial form of the enzyme is one of the most highly expressed genes in potato tubers, and the encoded product is imported into starch-synthesizing amyloplasts. We identified that the genomic locus of a Pho1a-type starch phosphorylase is duplicated in potato. Our study further shows that the enzyme is of importance for a normal starch granule phenotype in tubers. Null mutants created by genome editing display rounded starch granules in an increased number that contained a reduced ratio of apparent amylose in the starch.